2022
DOI: 10.1186/s12879-022-07546-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of the cagA and vacA s1m1 status and antibiotic resistance in Helicobacter pylori: a systematic review and meta-analysis

Abstract: Background The role of Helicobacter pylori (H. pylori) virulence factors of such as vacA s1m1 and cagA in designating clinical outcomes and eradication rate has been deeply challenged in the last decade. The goal of this analysis was to identify the potential relevance between cagA and vacA genotypes with reported antibiotic resistance observed in clinical H. pylori isolates. Methods This literature search was conducted in databases such as Clariva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 91 publications
0
8
0
2
Order By: Relevance
“…Our results showed that 72.7% of gastric adenocarcinoma samples were negative for p27 expression, which means that the lack of p27 expression can be an essential change during gastric carcinogenesis. More recent research indicates differential resistance of anti-microbial therapeutics worthy of further investigation between cagA positive and vacA positive H. pylori [62].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 72.7% of gastric adenocarcinoma samples were negative for p27 expression, which means that the lack of p27 expression can be an essential change during gastric carcinogenesis. More recent research indicates differential resistance of anti-microbial therapeutics worthy of further investigation between cagA positive and vacA positive H. pylori [62].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that 72.7% of gastric adenocarcinoma samples were negative for p27 expression, which means that the lack of p27 expression can be an essential change during gastric carcinogenesis. More recent research indicates differential resistance of anti-microbial therapeutics worthy of further investigation between cagA positive and vacA positive pylori [45].…”
Section: Discussionmentioning
confidence: 99%
“…Провідне місце в лікуванні виразкової хвороби відводиться антибактеріальному впливу на мікроорганізм H.pylori. Антибактеріальна терапія -найбільш жорстко регламентований у всьому світі розділ фармакотерапії [6]. Це продиктовано міркуваннями ефективності та безпеки використання медичної технології.…”
Section: резюмеunclassified